(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In recent years, there has been a sharp increase in attention to iodine deficiency conditions and diseases related to adequate iodine intake in the body. The concept of new iodine deficiency diseases has emerged, which includes not only thyroid diseases but also a number of pathological conditions associated with thyroid dysfunction. The issue of the interrelationship between thyroid and non-thyroid pathologies remains highly relevant.